2007
DOI: 10.1002/jcc.20715
|View full text |Cite
|
Sign up to set email alerts
|

Growth format, electronic architecture, magnetic, and optical properties of aromatic cyclo‐Cu3Au3 homotops

Abstract: Bimetallic Cu(3)Au(3) clusters have been investigated using electronic structure calculation techniques (DFT) to understand their electronic, magnetic, and optical properties as well as the geometrical structures. The most stable homotop is the planar cyclo-[Cu(3)(micro-Au)(3)] form consisting of a triangular positively charged Cu(3) structural core with negatively charged Au atoms occupying exposed positions. This structure is characterized by the maximum number of heterobonds and peripheral positions of Au a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 66 publications
1
6
0
Order By: Relevance
“…For binary alloy trimers triangular structures are the most stable forms with angles of 63.7° (∠AuAgAu), 57.4° (∠AgAuAg), 53.8° (∠CuAuCu), and 70.3° (∠AuCuAu) for Au 2 Ag, AuAg 2 , AuCu 2 , and Au 2 Cu clusters, respectively, and these results confirm previous studies. , …”
Section: Resultssupporting
confidence: 90%
“…For binary alloy trimers triangular structures are the most stable forms with angles of 63.7° (∠AuAgAu), 57.4° (∠AgAuAg), 53.8° (∠CuAuCu), and 70.3° (∠AuCuAu) for Au 2 Ag, AuAg 2 , AuCu 2 , and Au 2 Cu clusters, respectively, and these results confirm previous studies. , …”
Section: Resultssupporting
confidence: 90%
“…In a recent work, we showed that NICS profiles can be used to characterize aromaticity in inorganic species and to classify inorganic clusters into aromatic, nonaromatic, and antiaromatic categories 23. More recently, Stanger41 has checked the performance of this method for organic species and Tsipis et al42 have applied it to study cyclo‐ Cu 3 Au 3 homotops. In this work, we use NICS profiles to classify the studied compounds and to analyze the [X 2 M 3 ] regions where the changes in aromaticity as a function of the distance from the alkali metal to the center of the Mg 3 ring are more important.…”
Section: Computational Detailsmentioning
confidence: 99%
“…58 Recently, the NICS criterion has been successfully used to characterize aromaticity in inorganic species and to classify inorganic clusters into aromatic, nonaromatic, and antiaromatic categories. 59 Moreover, the performance of this method for organic species has been demonstrated 60 and Tsipis et al 61 have applied it to study cyclo-Cu 3 Au 3 bimetallic clusters. In addition, NICS profiles have been recently used to classify trigonal alkaline earth metal clusters and their alkali metal salts and to analyze the [X 2 M 3 ] regions where the changes in aromaticity are more important.…”
Section: Theoretical Dft Studymentioning
confidence: 99%